Clinical Advances of siRNA-Based Nanotherapeutics for Cancer Treatment - Dima Hattab; Amirah Mohd Gazzali; Athirah Bakhtiar (MDPI AG, 2021)
Cancer is associated with single or multiple gene defects. Recently, much research has focused on incorporating genetic materials as one of the means to treat various types of carcinomas. RNA interference (RNAi) conveys an alternative genetic approach for cancer patients, especially when conventional medications fail. RNAi involves the inhibition of expression of specific messenger RNA that signals for uncontrollable cell growth and proliferation, most notably with carcinoma cells. This molecular technology is promising as genetic materials allow us to overcome issues associated with chemotherapeutic agents including organ damage associated with severe drug toxicities. Nonetheless, vast challenges impede successful gene therapy application, including low tumor localization, low stability and rapid clearance from the blood circulation. Owing to the limited treatment opportunities for the management of cancer, the development of effective siRNA carrier systems involving nanotherapeutics has been extensively explored. Over the past years, several siRNA nanotherapeutics have undergone a period of clinical investigation, with some demonstrating promising antitumor activities and safety profiles. Extensive observation of siRNA-nanoparticles is necessary to ensure commercial success. Therefore, this review mainly focuses on the progress of siRNAs-loaded nanoparticles that have undergone clinical trials for cancer treatment. The status of the siRNA nanotherapeutics is discussed, allowing comprehensive understanding of their gene-mediated therapeutics.